The Implementation Of Character Education On Civics Education Subject For Inclusive Students - Novita Majid; Warman Warman; Wingkolatin Wingkolatin; Jepopi Selvia (Educational Studies: Conference Series, 2022)
This study aims to determine the problems of managing inclusive education in elementary schools in Kutai Kartanegara and formulate a model of inclusive school management. Currently, there are 2400 schools that are members of the Indonesian Integrated Islamic School Network. Almost all schools in Jakarta and West Java have been asked by the government to apply the concept of inclusive education, as well as several schools in other areas that have accepted children with special needs. Various problems arise, and it is felt necessary to find a solution to these problems. In particular, this research answers the questions, namely How to Implement Character Education in Civics Subjects for Inclusive Children. This study uses a qualitative research method with a case study approach. Data was collected through interviews, study of relevant documents and FGD with 6 school leaders from 3 schools providing inclusive education. The results of the study explain that each inclusive child has their own advantages or learning modalities, so that the learning and management services provided by the school adapt to the child's needs. Then for educators in inclusive schools there is also no need to be afraid because teaching students with special needs already has academic qualifications and competence standards. The inhibiting factors that occur in the implementation of character education in Civics subjects for inclusive students are internal factors (from students and school management), as well as external factors (derived from government policies and the implementation of inclusive education). the efforts made by schools in the implementation of character education in Civics subjects for inclusive students are: (1) schools still labeled with special needs children, services are provided by classroom teachers and special teachers work in teams; (2) schools without being labeled with ABK, services are provided by classroom/maple teachers equipped with PLB competencies and working in permanent teams; (3) learning in class is done individually, although there are some children who have the same learning needs; and (4) multimodality-based learning with a multilevel curriculum.